Ukuran Perusahaan, Pergantian Manajemen dan Pergantian Auditor pada Sektor Industri Dasar & Kimia - Qatrunnada Labibah; Lia Uzliawati; Roza Mulyadi (Jurnal Akuntansi, 2023)
The impartiality of the auditor is critical to the fairness evaluation of the audited financial accounts. The association of a company with a public accounting firm for a long time can affect the auditor's independence so as to allow for a certain relationship between the auditing company and the public accounting agency, but if it is too frequent, changing the independent auditor will increase the company's audit fees and indicate that the public accounting firm is not professional. There were 10 basic and chemical industry companies that changed their auditors more than once during the 2017–2021 period. Examining and analyzing the impact of company size and management shifts on auditor switching was the goal of this research. Chemical industry from 2017 to 2021, businesses will be listed on the IDX. This study used a quantitative approach, A sample size of 37 businesses, or 185 records, was obtained over the course of five years using the purposive selection method. With SPSS version 25, logistic regression is the data processing method used. Based on the findings of this study, (1) company size has no impact on changing auditors, and (2) managerial changes have no impact on changing auditors.Keywords: Company Size, Management Change, Auditor Switching